Hip Abduction Strength: Relationship to Trunk and Lower Extremity Motion During A Single-Leg Step-Down Task in Professional Baseball Players - M. Christopher Zipser; Hillary A Plummer; Nathan Kindstrand; Johnathan C Sum; Bernard Li; Lori A Michener (North American Sports Medicine Institute, 2021)
# Background The single-leg step down task (SLSD) is a clinical tool to assess movement and control of the lower extremity and trunk. Hip abduction weakness may impact movement quality during the SLSD, however the relationships between movement and strength are unclear. # Purpose To determine the relationship between hip abduction isometric strength and movement during the SLSD of trunk lean, pelvic drop, knee valgus, and hip flexion. # Study Design Cross sectional, cohort study # Methods One hundred-eighteen Minor League baseball players (age=21.6 ± 2.0 years; n=68 pitchers, n=50 position players) participated. Bilateral hip abduction isometric strength was measured using a handheld dynamometer (HHD), and then multiplied by distance from the greater trochanter to the HHD and expressed as hip abduction torque. Video cameras captured the SLSD, with participants standing on one leg while lowering their contralateral heel to touchdown on the floor from a 0.203m (8in.) step. Trunk lean, trunk flexion, pelvic drop, knee valgus, and hip flexion were measured using Dartfish at heel touchdown. A value of 180° indicated no knee valgus. Pearson correlations examined the relationships between hip abduction torque and SLSD motions. # Results There were no significant correlations for position players. For pitchers, on the lead leg increased hip abduction torque weakly correlated with a decrease in knee valgus (r= 0.24, p=0.049). Also for pitchers on the trail leg, increased hip abduction torque weakly correlated with decreased pelvic drop (r= -0.28, p=0.021). # Conclusion Hip abduction strength contributes to dynamic control of the trunk and legs. Specifically in pitchers, hip abduction weakness was related to increased movement of the lower extremity and lumbopelvic regions during the dynamic SLSD task. These deficits could translate to altered pitching performance and injury. # Levels of Evidence 2\.